Method for preparing low-carbon water-permeable bricks by alkali-activated synergistic microbial technology

CN118388211BActive Publication Date: 2026-10-27UNIV OF SCI & TECH BEIJING
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202410672941.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2026-10-27
Estimated Expiration
2044-05-28

AI Technical Summary

Technical Problem

[0010]综上,现有的固体废弃物无害化处置和资源化利用均存在低利用率、高成本,结合微生物制备的建材砖工艺存在复杂、可操作性差、能耗高等问题,亟需研发高掺量固体废弃物绿色制备低碳透水砖的方法,充分利用固体废弃物中的硅铝酸盐成分,结合申请人前期制备碱激发胶凝材料技术以及微生物胶结技术制备低碳透水砖是实现固体废弃物综合利用的有效途径

Benefits of technology

[0023](1)本发明所述方法中采用固体废弃物中的SiO2、Al2O3作为硅源和铝源,减少了原材料消耗,同时添加的NaOH溶液能够与固体废弃物中的硅铝酸盐和无定型态SiO2等反应生成硅铝酸钠、硅铝酸钙等凝胶体。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118388211B_ABST
    Figure CN118388211B_ABST
Patent Text Reader

Abstract

The application provides a method for preparing low-carbon water-permeable bricks by alkali-activated synergistic microbial technology, relates to the field of solid waste disposal and utilization, and comprises the following steps: (1) uniformly mixing silicate solid waste and a NaOH solution, and forming an alkali-activated cementing body after reaction; (2) adding microbial bacteria liquid to the alkali-activated cementing body, and performing compression molding, once standing and demolding to obtain a green body; and (3) performing once curing of the green body in nutrient liquid, continuing to spray the microbial bacteria liquid after taking out the green body, performing twice standing, and then immersing the green body in nutrient liquid to perform twice curing, so that the low-carbon water-permeable bricks are obtained. The water-permeable bricks prepared by the method have excellent performances such as large water permeability coefficient, corrosion resistance and strong freeze-thaw resistance, can reduce urban drainage pressure in extreme environments, and are applied to sponge city construction. The application uses solid waste as raw material, realizes harmless and high value of the solid waste, has the advantages of simple process flow, no need of high-temperature calcination, low carbon emission and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid waste disposal and utilization, specifically to a method for preparing low-carbon permeable bricks using alkali-activated synergistic microbial technology. Background Technology

[0002] Industrial solid waste comprises slag, waste materials, and waste sand generated during industrial production processes. It mainly consists of raw materials, additives, and byproducts from the production process, exhibiting a complex composition. Slag and waste sand in solid waste are predominantly composed of aluminosilicates, exhibiting a dual nature of resource and environmental impact. On the one hand, the silica and alumina present in solid waste are valuable oxide resources; on the other hand, the harmful elements in solid waste can easily pollute the environment. The disposal of solid waste has become one of the major issues restricting the healthy development of industry, necessitating urgent research and development of green disposal and high-value utilization technologies.

[0003] The essence of solid waste resource utilization is to separate and extract target metals and comprehensively utilize oxides through physical means, pyrometallurgical or hydrometallurgical processes. From the perspective of the quantity of solid waste disposed of, using solid waste to produce building materials can promote the green, low-carbon, and circular development of industry and help ensure the secure supply of resources.

[0004] Chinese invention patent CN 107021723 A discloses a method for mixing an aqueous solution containing microbial powder, sand, stainless steel slag, and lime into a slurry, pressing it into shape at 10~30 MPa, and then placing it in a pressure vessel for curing for 4~6 hours at a relative humidity of 70±3% and a CO2 pressure of 0.2~0.3 MPa to obtain stainless steel slag bricks with a strength of 35~39 MPa.

[0005] Chinese invention patent CN 1101183194 A discloses a method for preparing microbial-steel slag carbon-fixing permeable bricks. After mixing and stirring steel slag coarse aggregate and dilute acetic acid, steel slag micro powder and microbial powder are introduced and poured into a mold. The mixture is pressed into shape at 20~40 MPa, cured at 25±2℃ and humidity above 95% for 8 hours, demolded, and then cured in a pressure vessel under CO2 atmosphere for 18 hours to obtain permeable bricks. The beneficial effects of the above two patents include the ability to adsorb CO2 and excellent mechanical properties. However, both require a specific pressure vessel and a continuous supply of CO2, making the process complex and the raw materials used limited, thus narrowing the application scope.

[0006] Chinese invention patent CN 107540338 A discloses a method for manufacturing microbial bricks from waste incineration ash. The method involves sieving waste incineration ash, selecting ash particles smaller than 5 mm, mixing them evenly with a bacterial solution at an OD600 concentration of 1.2, filling the mixture into a porous, permeable mold, and then compacting it. The mold is then immersed in a mixture of urea and CaCl2 at equimolar concentrations of 0.8–1.2 mol / L to prepare the waste incineration ash microbial bricks. However, this invention has a narrow applicability, only targeting waste incineration ash as a solid waste. Furthermore, the strength of the waste incineration ash particles is relatively low due to the reliance on calcium carbonate crystals induced by microorganisms for bonding. In contrast, this invention utilizes alkali-activated pretreatment to form gels such as sodium aluminosilicate and calcium aluminosilicate, resulting in a significantly improved network cross-linked structure.

[0007] Chinese invention patent CN 108748623 A discloses a high-efficiency molding method for high-pressure microbial soil-stabilized hollow bricks. This invention uses geotextile and perforated plexiglass plates to make lightweight molds, then fills the molds with sand and bacteria, and uses PVC pipes to make hollow structures to obtain hollow bricks. Although this method is simple and efficient, relying solely on microbial bonding can easily cause clay bricks to break and result in low utilization of solid waste.

[0008] Chinese invention patent CN 105294051 B discloses a method and apparatus for preparing microbial coral sand bricks. This invention discloses the process of adding water to domesticated and preserved Bacillus Pasteurella multocida to prepare a solution with an activity greater than 1 mM·min⁻¹. -1 Prepare the bacterial solution and adjust the pH to 7-8. Then, mix the bacterial solution with a 1 mol·L⁻¹ solution. -1 Calcium chloride and 1 mol·L -1 The solidified solution formed by mixing urea solution in a volume ratio of 1:1:1 is mixed with coral sand particles, and then the solidification reaction is carried out in an electrochemical environment of 3-4V for 6 hours. The positive and negative electrodes need to be exchanged 2-3 times, and the electrochemical process is repeated 6-8 times. After demolding and drying, coral sand bricks are obtained. This method is highly innovative, using current to guide ions in the culture medium in a directional manner. However, it introduces multiple electrochemical processes, resulting in high energy consumption, complex process, and poor operability.

[0009] Chinese invention patent CN 113664974 A discloses a method for producing injection-type microbial clay bricks. The method uses clay and basalt fiber as raw materials, and then injects a mixture (bacteria and nutrient solution) twice. After four days of reaction, the injection of the mixture is stopped. The beneficial effect of this patent is that it does not require high-temperature sintering, and the addition of basalt fiber improves the mechanical properties. However, the clay bricks prepared by the patent are solid structures and their mechanical properties are still significantly different from those of traditional concrete bricks, and they do not have water permeability.

[0010] In summary, existing methods for the harmless disposal and resource utilization of solid waste suffer from low utilization rates and high costs. The process of preparing building materials bricks using microorganisms is complex, has poor operability, and high energy consumption. There is an urgent need to develop a method for the green preparation of low-carbon permeable bricks using high-volume solid waste. Fully utilizing the aluminosilicate components in solid waste and combining the applicant's previous technology for preparing alkali-activated cementitious materials and microbial bonding technology to prepare low-carbon permeable bricks is an effective way to achieve comprehensive utilization of solid waste. Summary of the Invention

[0011] The purpose of this invention is to fully utilize the compositional characteristics of solid waste, destroy the structure of aluminosilicates in solid waste through alkali activation, and then repolymerize them to form a network. By utilizing the alkali activation mechanism and the calcium carbonate conversion reaction induced by microbial carbonic anhydrase, a composite crystalline phase of calcium carbonate-gel is formed by combining microbial-alkali activation technology, a high-strength mechanical property system is constructed, and a permeable brick is formed. By combining microbial technology with materials science technology, the high-value utilization of solid waste is achieved.

[0012] This invention is achieved through the following technical solution:

[0013] A method for preparing low-carbon permeable bricks using alkali-activated synergistic microbial technology includes the following steps:

[0014] (1) Mix aluminosilicate solid waste with NaOH solution. After the reaction, an alkali-activated gel is formed, which helps to improve mechanical properties;

[0015] (2) Add microbial liquid to the alkali-activated gel obtained in step (1), press and shape it, and then let it stand and demold to obtain the green body;

[0016] (3) The green body obtained in step (2) is cured in nutrient solution once. After the green body is removed, microbial liquid is sprayed on it again. After being left to stand for a second time, it is immersed in nutrient solution for a second curing to obtain the low carbon permeable brick.

[0017] Further, in step (1), the aluminosilicate solid waste is selected from one or more of sand and gravel, construction waste, stainless steel slag, fly ash, waste incineration bottom ash, and ferrosilicon manganese alloy slag. All of these substances are general solid wastes rich in aluminosilicates, with a particle size of 0.1-5 mm. The NaOH solution concentration is 0.5-1.5 mol / L, the amount added is 10-30% of the aluminosilicate solid waste mass, and the alkali-activated reaction time is 4-12 h, forming gels such as sodium aluminosilicate and calcium aluminosilicate.

[0018] Further, in step (2), the microbial solution is a bacterium capable of inducing calcium carbonate precipitation, such as Bacillus pasteurellii, Bacillus subtilis, Sporosarcinapasteurii, etc. The amount of the microbial solution added is 3-10% of the total mass of aluminosilicate solid waste and NaOH solution, the OD600 value of the solution is 0.6-1.2, the settling time is 5-12 h, and the pressing pressure is 15-20 MPa.

[0019] Further, in step (3), the nutrient solution is a solution of 0.1~0.5 mol / L urea and calcium salt solution of the same molar concentration, wherein the calcium salt is selected from one or more of calcium chloride, calcium lactate and calcium bicarbonate, and the maintenance time is 48-72 h.

[0020] Further, in step (3), the amount of microbial inoculum added is 5-8% of the total mass of the mixture of aluminosilicate solid waste and NaOH solution, the OD600 value of the inoculum is 0.6-1.2, the second settling time is 12-24 h, and the second curing time is 48-72 h. The present invention's secondary curing and the secondary addition of microbial inoculum during the curing process can reduce the probability of uneven contact between particles and the liquid phase due to liquid penetration, and improve the distribution area and precipitation rate of the gel-calcium carbonate composite crystal phase.

[0021] The present invention also provides low-carbon permeable bricks prepared by the method.

[0022] The beneficial technical effects of the present invention are as follows:

[0023] (1) The method described in this invention uses SiO2 and Al2O3 in solid waste as silicon and aluminum sources, which reduces the consumption of raw materials. At the same time, the added NaOH solution can react with aluminosilicates and amorphous SiO2 in solid waste to generate gels such as sodium aluminosilicate and calcium aluminosilicate.

[0024] (2) The carbonic anhydrase precipitated by microorganisms in the method of the present invention can induce Ca in the nutrient solution. 2+ CO3 2- HCO3 - This leads to the formation of CaCO3, while the Ca in the nutrient solution... 2+ It can simultaneously participate in the formation of calcium-containing gels in the alkali-activated system, thereby forming a calcium carbonate-gel composite structure, which is beneficial to improving the mechanical properties of low-carbon bricks.

[0025] (3) The method described in this invention transforms solid waste into building materials without the need for heat treatment, saving costs compared to processes such as pyrometallurgical, wet, and physical sorting, saving a significant amount of land compared to traditional landfilling, and transforming solid waste into valuable products. The composite structure of calcium carbonate and gel can further prevent harmful elements in solid waste from entering the environment, further achieving the harmless disposal of solid waste.

[0026] (4) The present invention has the advantages of simple process, low cost, no pollution and wide applicability. The low carbon permeable bricks prepared meet the requirements of the national standard (GB / T 25993-2010) "Permeable pavement bricks and permeable pavement panels", and can be applied to the construction of sponge cities to reduce drainage pressure in complex environments. Attached Figure Description

[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1 These are SEM images of the gel-carbonate composite crystal particles formed in the preparation of the brick provided in Example 1 of the present invention, wherein (a) is magnified by 5000 times and (b) is magnified by 10000 times. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.

[0030] Conversely, this invention encompasses any substitutions, modifications, equivalent methods, and solutions made within the spirit and scope of the invention as defined in the claims. Furthermore, to provide a better understanding of the invention, certain specific details are described in detail below. However, those skilled in the art will fully understand the invention even without these detailed descriptions.

[0031] Comparative Example 1

[0032] Waste incineration bottom ash with a particle size of 0.1-5 mm was selected and mixed with 10% of the total mass of solid waste in 0.5 mol / L NaOH solution. The alkaline activation reaction was carried out for 12 h. Then, Sporosarcina pasteurii bacterial solution (OD600=0.80) was added at 3% of the total mass of the mixture of solid waste and NaOH solution. The mixture was allowed to stand for 12 h and then pressed into bricks at a pressure of 15 MPa. The pressed bricks were then placed in a nutrient solution of 0.1 mol / L urea and calcium chloride of the same molar concentration and cured for 72 h. The flexural strength reached 0.65 MPa. However, the mechanical properties did not meet the standards because a second spraying of bacterial solution and a second curing were not carried out.

[0033] Comparative Example 2

[0034] Waste incineration bottom ash with a particle size of 0.1-5 mm was selected and mixed with 10% of the total mass of solid waste in 0.5 mol / L NaOH solution. The alkaline activation reaction was carried out for 12 h. Then, Sporosarcina pasteurii bacterial solution (OD600=0.80) was added at 3% of the total mass of the solid waste and NaOH solution mixture. The mixture was allowed to stand for 12 h and then pressed into bricks at a pressure of 15 MPa. The pressed bricks were then placed in a nutrient solution of 0.1 mol / L urea and calcium chloride of the same molar concentration for 72 h of curing and a second curing time of 48 h. The flexural strength reached 0.81 MPa. The mechanical properties did not meet the standards because a second spraying of bacterial solution was not carried out.

[0035] Example 1

[0036] Waste incineration bottom ash with a particle size of 0.1-5 mm was selected and mixed with 10% of the total mass of solid waste in 0.5 mol / L NaOH solution. The alkaline activation reaction was carried out for 12 h. Then, 3% of the total mass of the solid waste and NaOH solution mixture in Sporosarcina pasteurii bacterial solution (OD600=0.80) was added. The mixture was allowed to stand for 12 h and then pressed into bricks at a pressure of 15 MPa. The pressed bricks were then placed in a nutrient solution of 0.1 mol / L urea and calcium chloride of the same molar concentration for 72 h. After that, the mixture was sprayed with 5% of the total mass of the solid waste and NaOH solution mixture in Sporosarcina pasteurii bacterial solution (OD600=1.10) and allowed to stand for 12 h. The secondary curing time was 48 h. The flexural strength reached 3.5 MPa and the permeability coefficient was 0.23 cm / s, achieving Class A permeability.

[0037] Figure 1These are SEM images of the gel-carbonate composite crystal particles formed in the preparation of bricks according to Example 1 of this invention, where (a) is magnified 5000 times and (b) is magnified 10000 times. The images show particulate raw materials from waste incineration bottom ash, as well as the subsequently formed calcium carbonate and gel regions.

[0038] Example 2

[0039] Fly ash with a particle size of 0.1-5 mm was selected and mixed with 20% of the total mass of solid waste in a 0.6 mol / L NaOH solution. The mixture was subjected to an alkaline activation reaction for 12 h. Then, 4% of the total mass of the solid waste and NaOH solution mixture was added with Sporosarcina pasteurii bacterial solution (OD600=0.70). The mixture was allowed to stand for 11 h, and then pressed into bricks at a pressure of 16 MPa. The pressed bricks were then placed in a nutrient solution of 0.2 mol / L urea and calcium bicarbonate of the same molar concentration for 72 h. Afterward, the mixture was sprayed with 6% of the total mass of the solid waste and NaOH solution mixture in Sporosarcina pasteurii bacterial solution (OD600=0.90), allowed to stand for 18 h, and then subjected to a second curing for 48 h. The flexural strength reached 3.3 MPa and the permeability coefficient was 0.24 cm / s, achieving a Class A permeability rating.

[0040] Example 3

[0041] Stainless steel slag with a particle size of 0.1-5 mm was selected and mixed with 14% of the total mass of solid waste in a 0.7 mol / L NaOH solution. The reaction was initiated with alkali for 10 h. Then, 5% of the total mass of the solid waste and NaOH solution mixture was mixed with Bacillus cohnii bacterial solution (OD600=0.60). The mixture was allowed to stand for 10 h and then pressed into bricks at a pressure of 17 MPa. The pressed bricks were then placed in a nutrient solution of 0.3 mol / L urea and calcium lactate of the same molar concentration for 70 h. Afterward, the mixture was sprayed with 7% of the total mass of the solid waste and NaOH solution mixture in Bacillus cohnii bacterial solution (OD600=1.20). The mixture was allowed to stand for 14 h and then cured for a second time for 60 h. The flexural strength reached 3.4 MPa and the permeability coefficient was 0.18 cm / s, achieving a Class B permeability rating.

[0042] Example 4

[0043] A mixture of waste incineration bottom ash and stainless steel slag with a particle size of 0.1-5 mm was selected and mixed with 16% of the total mass of solid waste in 0.8 mol / L NaOH solution. The mixture was subjected to an alkaline activation reaction for 9 h. Then, 6% of the total mass of the solid waste and NaOH solution mixture in Bacillus subtilis bacterial solution (OD600=0.85) was added, and the mixture was allowed to stand for 9 h. The pressing pressure was 20 MPa. The pressed bricks were then placed in a nutrient solution of 0.4 mol / L urea and calcium chloride of the same molar concentration for 70 h. Afterward, 8% of the total mass of the solid waste and NaOH solution mixture in Bacillus subtilis bacterial solution (OD600=1.10) was sprayed on the bricks, and the mixture was allowed to stand for 16 h. The secondary curing time was 72 h. The flexural strength reached 4.0 MPa, and the permeability coefficient was 0.20 cm / s, achieving a Class A permeability rating.

[0044] Example 5

[0045] A mixture of sand and gravel with a particle size of 0.1-5 mm and waste incineration bottom ash was selected and mixed with 20% of the total mass of solid waste in 0.9 mol / L NaOH solution. The mixture was subjected to an alkali-activated reaction for 8 hours. Then, 7% of the total mass of the solid waste and NaOH solution mixture was added with Bacillus subtilis bacterial solution (OD600=0.95). The mixture was allowed to stand for 8 hours, and then pressed into bricks at a pressure of 18 MPa. The pressed bricks were then placed in a nutrient solution of 0.5 mol / L urea and calcium chloride and calcium lactate of equal molar concentration for 48 hours of curing. Afterward, the mixture was sprayed with 7% of the total mass of the solid waste and NaOH solution mixture with Bacillus subtilis bacterial solution (OD600=1.15), and allowed to stand for 20 hours. The secondary curing time was 70 hours. The flexural strength reached 3.31 MPa, and the permeability coefficient was 0.25 cm / s, achieving a Class A permeability rating.

[0046] Example 6

[0047] A mixture of sand and gravel with a particle size of 0.1-5 mm and construction waste was selected and mixed with 25% of the total mass of solid waste in a 1 mol / L NaOH solution. The mixture was subjected to an alkaline activation reaction for 7 hours. Then, 8% of the total mass of the solid waste and NaOH solution mixture was added with Bacillus cohnii bacterial solution (OD600=0.75). The mixture was allowed to stand for 7 hours, and then pressed into bricks at a pressure of 19 MPa. The pressed bricks were then placed in a nutrient solution of 0.15 mol / L urea and calcium chloride of the same molar concentration for 68 hours of curing. Afterward, 6% of the total mass of the solid waste and NaOH solution mixture was sprayed with Bacillus cohnii bacterial solution (OD600=1.01), and the mixture was allowed to stand for 22 hours. A second curing period of 62 hours was then achieved. The flexural strength reached 3.41 MPa, and the permeability coefficient was 0.23 cm / s, achieving a Class A permeability rating.

[0048] Example 7

[0049] Silicate manganese alloy slag with a particle size of 0.1-5 mm was selected and mixed with 30% of the total mass of solid waste in a 1.1 mol / L NaOH solution. The reaction was initiated with alkali for 6 h. Then, 10% of the total mass of the solid waste and NaOH solution mixture was mixed with Bacillus subtilis bacterial solution (OD600=1.15). The mixture was allowed to stand for 5 h and then pressed at a pressure of 17 MPa. The pressed bricks were then placed in a nutrient solution of 0.25 mol / L urea and calcium lactate of the same molar concentration for 66 h. After that, the bricks were sprayed with 5.5% of the total mass of the solid waste and NaOH solution mixture in Bacillus subtilis bacterial solution (OD600=1.11). The mixture was allowed to stand for 23 h and then cured for a second time for 66 h. The flexural strength reached 3.33 MPa and the permeability coefficient was 0.26 cm / s, achieving a Class A permeability rating.

[0050] Example 8

[0051] A mixture of fly ash and ferrosilicon manganese alloy slag with a particle size of 0.1-5 mm was selected and mixed with 26% of the total mass of solid waste in a 1.5 mol / L NaOH solution. The mixture was subjected to an alkaline activation reaction for 4 hours. Then, 6.5% of the total mass of the solid waste and NaOH solution mixture in a Bacillus cohnii bacterial solution (OD600=0.75) was added, and the mixture was allowed to stand for 6 hours. The pressing pressure was 20 MPa. The pressed bricks were then placed in a nutrient solution of 0.35 mol / L urea and calcium chloride of the same molar concentration for 52 hours of curing. Afterward, a further spraying with 6.5% of the total mass of the solid waste and NaOH solution mixture in a Bacillus subtilis bacterial solution (OD600=1.2) was applied, and the mixture was allowed to stand for 24 hours. The secondary curing time was 68 hours. The flexural strength reached 3.26 MPa, and the permeability coefficient was 0.27 cm / s, achieving a Class A permeability rating.

[0052] Example 9

[0053] Waste incineration bottom ash and fly ash with a particle size of 0.1-5 mm were selected and mixed with 16% of the total mass of solid waste in 0.55 mol / L NaOH solution. The alkaline activation reaction was carried out for 12 h. Then, 5.5% of the total mass of the solid waste and NaOH solution mixture in Bacillus cohnii bacterial solution (OD600=0.85) was added. The mixture was allowed to stand for 8 h and then pressed into bricks at a pressure of 18 MPa. The pressed bricks were then placed in a nutrient solution of 0.45 mol / L urea and calcium chloride of the same molar concentration for 50 h. After that, the mixture was sprayed with 7.5% of the total mass of the solid waste and NaOH solution mixture in Sporosarcina pasteurii bacterial solution (OD600=0.98). The mixture was allowed to stand for 21 h and then cured for 67 h. The flexural strength reached 3.41 MPa, the permeability coefficient was 0.26 cm / s, and the compressive strength reached 37 MPa.

[0054] Example 10

[0055] Sand and gravel with a particle size of 0.1-5 mm were selected and mixed with 18% of the total mass of solid waste in a 0.65 mol / L NaOH solution. The alkaline activation reaction was carried out for 11 h. Then, 7.5% of the total mass of the solid waste and NaOH solution mixture in Bacillus scohnii bacterial solution (OD600=0.91) was added. The mixture was allowed to stand for 9.5 h and then pressed into bricks at a pressure of 17 MPa. The pressed bricks were then placed in a nutrient solution of 0.27 mol / L urea and calcium lactate of the same molar concentration for 65 h. After that, the mixture was sprayed with 8% of the total mass of the solid waste and NaOH solution mixture in Sporosarcina pasteurii bacterial solution (OD600=1.18) and allowed to stand for 15 h. The secondary curing time was 55 h. The flexural strength reached 3.55 MPa and the permeability coefficient was 0.21 cm / s, achieving a Class A permeability rating.

[0056] Example 11

[0057] Construction waste with a particle size of 0.1-5 mm was selected and mixed with 22% of the total mass of solid waste in a 0.75 mol / L NaOH solution. The reaction was initiated with alkali for 5 hours. Then, 9% of the total mass of the solid waste and NaOH solution mixture was added with Bacillus scohnii bacterial solution (OD600=0.93). The mixture was allowed to stand for 5.5 hours, and then pressed at a pressure of 16 MPa. The pressed bricks were then placed in a nutrient solution of 0.38 mol / L urea and calcium chloride and calcium bicarbonate of equal molar concentration for 55 hours of curing. Afterward, 7% of the total mass of the solid waste and NaOH solution mixture was sprayed with Bacillus subtilis bacterial solution (OD600=1.11), and the mixture was allowed to stand for 12 hours. The second curing time was 58 hours. The flexural strength reached 3.11 MPa, and the permeability coefficient was 0.26 cm / s, achieving a Class A permeability rating.

[0058] Example 12

[0059] A mixture of fly ash and construction waste with a particle size of 0.1-5 mm was selected and mixed with 26% of the total mass of solid waste in a 0.55 mol / L NaOH solution. The mixture was subjected to an alkaline activation reaction for 6 hours. Then, 8% of the total mass of the solid waste and NaOH solution mixture in a Sporosarcina pasteurii bacterial solution (OD600=0.88) was added, and the mixture was allowed to stand for 5.5 hours. The pressing pressure was 17 MPa. The pressed bricks were then placed in a nutrient solution of 0.38 mol / L urea and calcium chloride and calcium lactate of equal molar concentration for 55 hours of curing. Afterward, a 7% Bacillus cohnii bacterial solution (OD600=0.93) of the total mass of the solid waste and NaOH solution mixture was sprayed on the bricks, and the mixture was allowed to stand for 12 hours. The second curing time was 55 hours. The flexural strength reached 3.07 MPa, and the permeability coefficient was 0.28 cm / s, achieving a Class A permeability rating.

[0060] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing low-carbon permeable bricks using alkali-activated synergistic microbial technology, characterized in that, Includes the following steps: (1) Mix aluminosilicate solid waste with NaOH solution and react to form alkali-activated gel; (2) Add microbial liquid to the alkali-activated gel obtained in step (1), press and shape it, and then let it stand and demold to obtain the green body; (3) The green body obtained in step (2) is cured in nutrient solution once. After the green body is removed, microbial liquid is sprayed on it again. After a second settling, it is immersed in nutrient solution for a second curing to obtain the low-carbon permeable brick. In step (1), the aluminosilicate solid waste is selected from one or more of sand and gravel, construction waste, stainless steel slag, fly ash, waste incineration bottom ash, and ferrosilicon manganese alloy slag; In step (1), the concentration of the NaOH solution is 0.5~1.5 mol / L, the amount added is 10~30% of the amount of aluminosilicate solid waste, and the alkaline activation reaction time is 4~12 h; In step (2), the amount of microbial inoculum added is 3-10% of the total mass of aluminosilicate solid waste and NaOH solution, and the OD600 value of the inoculum is 0.6-1.2; the settling time is 5-12 h, and the pressing pressure is 15-20 MPa. In step (3), the amount of microbial inoculum added is 5-8% of the total mass of the mixture of aluminosilicate solid waste and NaOH solution, and the OD600 value of the inoculum is 0.6-1.2; the nutrient solution is 0.1-0.5 mol / L urea and calcium salt solution of the same molar concentration, wherein the calcium salt is selected from one or more of calcium chloride, calcium lactate and calcium bicarbonate, and the first curing time is 48-72h; the second settling time is 12-24h, and the second curing time is 48-72h.

2. The method for preparing low-carbon permeable bricks using alkali-activated synergistic microbial technology according to claim 1, characterized in that, In step (2), the microbial culture is a bacterium that can induce calcium carbonate precipitation, selected from at least one of Bacillus pasteurellii and Bacillus coli.

3. The low-carbon permeable brick prepared by the method described in claim 1 or 2.

Citation Information

Patent Citations

  • Preparation method and device of microbial coral sand brick

    CN105294051B

  • Method for preparing microbial mineralized stainless-steel-slag bricks

    CN107021723A

  • Method for efficiently forming hollow bricks through high-pressure microorganism solid soil

    CN108748623A

  • Method for producing injected microbial clay brick

    CN113664974A

  • Method used for preparing solid waste building material products based on microorganism mineralization induction technology

    CN105481469A